STRATEGI PENGELOLAAN KESAN DALAM KOMUNIKASI HYPERPERSONAL PENGGUNA TINDER - Nugroho, Fadilah; Hasfi, Nurul (Interaksi Online, 2019)
Users of the Tinder online dating application, through a series of impression management strategies, seek to realize hyperpersonal interactions so that interpersonal relationships can be formed. This study aims to describe the interactions in hyperpersonal communication and the impression management strategy displayed to other users. The research method uses descriptive qualitative with primary data sources from in-depth interviews with 6 Tinder users who managed to meet in person / date with other users. The data analysis technique used is the filling system technique. The result of the study show: (1) Interaction in hyperpersonal communication of Tinder users occurs when the informants do selective self-presentations, receive messages by making overattribution of similarity, utilize channels to communicate in their own time, and the feedback is self-fulfilling prophecy ( 2) In this interaction, Tinder users use four main strategies which are ingratiation to show themselves to be personally attractive so as to be liked, self-promotion to show the impression that they are competent for a particular skill, exemplification ensures that they are moral and trustworthy, and supplication to get empathy from the other users.